Public Perception of Television News Coverage on the Vina Cirebon Case: A Case Study of TVOne Broadcasts in RT 006, Gunung Agung, Bandar Lampung - Daniati, Rachma; Verawati, Noning; Pienrasmi, Hanindyalaila (Interaction Communication Studies Journal, 2025)
This study examines the public perception of the news coverage regarding the Vina Cirebon case aired on TVOne. The case of Vina, a 16-year-old student from Cirebon, drew widespread attention after a film titled "Vina Sebelum 7 Hari" revived public discussion on the unresolved murder case. Using a qualitative approach, this study explores how viewers in RT 006 Gunung Agung interpreted and responded to TVOne’s coverage, including news programs and special segments like “Dua Sisi”. Data was gathered through interviews with selected informants using purposive sampling. The findings reveal that viewers formed both positive and negative perceptions. Positive responses include increased public awareness and caution regarding personal safety, while negative responses involve skepticism towards law enforcement and the legal system due to the prolonged nature and inconsistencies in the case handling. These findings suggest a need for more responsible media framing and for the public to maintain a critical but balanced view of media content.